Moral harassment at work: an exploratory study in Fortaleza city - Benevides, Samira Daiha; Matos, Fátima Regina Ney; Figueiredo, Nemias Cardoso; Lopes, Kátia Lene de Araújo (Revista de Administração da UFSM, 2012)
http://dx.doi.org/10.5902/198346592455 The objective of this article is to present the incidence of the cases of moral harassment in Fortaleza city using the data base of complaints registered for the victims in the Delegacia Regional do Trabalho in the period of January of 2008 the December of 2009. The literature review is based on the moral harassment, its legal manifestations, as well as the psychic structures of defense of the worker. A exploratory research with the use of secondary data was made in the Nucleus of Combat was become fullfilled the Discrimination through the monthly report of the denunciations of moral harassment elaborated by the Regional Commission of Equality of Chances of Gender, Race and ethnic group, of People with Deficiency and Combat to the Discrimination. The results had been demonstrated through graphs that had evaluated the type of discrimination for moral harassment, for professional profile, for sex and age of the plaintiff. The workers had more passed not to accept offences and behaviors that offend its dignity, demanding to be respected It can be concluded that still it has discrimination in some areas, generating many times behaviors undesirable and abusive behaviors, degrading the work climate and reducing the productivity.